1995
DOI: 10.1288/00005537-199511000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Modified transnasal endoscopic lothrop procedure: Further considerations

Abstract: The Lothrop procedure resects the medial frontal sinus floor, superior nasal septum, and intersinus septum to create a large frontonasal communication. However, the external approach often allowed medial collapse of soft tissue and stenosis of the nasofrontal communication. We describe a modified transnasal endoscopic Lothrop procedure in which drills are used for cases in which frontal recess exploration fails to relieve obstruction of the frontal sinus. The lateral bony walls are preserved, and medial collap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 16 publications
0
44
0
3
Order By: Relevance
“…A bilateral drillout procedure creates a surgical opening that is twice the size and may be less susceptible to postoperative closure. Becker et al 18 reported no ostial closure in 14 patients who underwent bilateral frontal drillout with a mean follow-up of 9 months; however, frontal headaches recurred in 2 patients (14.3%). Close et al 9 reported symptoms of recurrent rhinosinusitis in 1 of 7 patients who underwent frontal sinus drillout who had been followed up for at least 3 months for a similar short-term failure rate of 14.3%.…”
mentioning
confidence: 99%
“…A bilateral drillout procedure creates a surgical opening that is twice the size and may be less susceptible to postoperative closure. Becker et al 18 reported no ostial closure in 14 patients who underwent bilateral frontal drillout with a mean follow-up of 9 months; however, frontal headaches recurred in 2 patients (14.3%). Close et al 9 reported symptoms of recurrent rhinosinusitis in 1 of 7 patients who underwent frontal sinus drillout who had been followed up for at least 3 months for a similar short-term failure rate of 14.3%.…”
mentioning
confidence: 99%
“…Previous studies have emphasized the importance of creating a large drainage pathway to reduce the risk of stenosis and obliteration of the frontal ostium [3,4,7]. In our series, although we avoided bone resection in the lateral and anterior aspect of the frontal recess and frontonasal duct, a drainage pathway is patent in all patients.…”
Section: Discussionmentioning
confidence: 77%
“…The EMLP was first described by Draf [6], and was later popularized by Gross et al [3,4]. This technique makes a common drainage pathway for both frontal sinuses after resection of the upper nasal septum, interfrontal sinus septum, and frontal sinus floor by a drill.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, functional endoscopic sinus surgery has been accepted as the procedure of choice for the surgical treatment of chronic sinusitis. [1][2][3][4] However, because of the unique and complex anatomy of the frontoethmoidal recess and its anatomical relationship to adjacent vital structures, the treatment of the frontal sinus diseases still remains a challenge. The risks associated with overly aggressive instrumentation in this region furthermore highlight the need for minimally traumatic techniques to reduce the risk of postoperative stenosis.…”
Section: Introductionmentioning
confidence: 99%